Application of feed seawater overflush in three-cylinder valve-controlled energy recovery device - Zheng Sun; Chunfang Liao; Xinghong Liu; Yan Xiao; Sijie Lin; Zhigang Mai; Jing Yang (Desalination and Water Treatment, 2025)
The three-cylinder valve-controlled energy recovery device (TC-ERD) employs “liquid piston” instead of physical piston, which improves operational safety but also reduces the volumetric efficiency of the pressure exchange cylinder. Herein, a method of feed seawater overflush is proposed, which can inhibit the accumulation and expansion of brine/seawater mixing zone during each stroke alternation to reduce the brine/seawater volume mixing degree, laying the foundation for improving the cylinder volumetric efficiency and the processing capacity of the TC-ERD. The relationship among overflush rate (OR), maximum volume mixing degree (Vm-max) and cylinder volumetric efficiency (UR) is fitted, which can provide guidance for the rational operation of the TC-ERD. When the OR increases from 0 % to 5 %, the UR rises from 57.98 % to 82.1 %, the maximum processing capacity increases from 33.1 m3/h to 46.9 m3/h, while the energy recovery efficiency only decreases from 97.05 % to 94.04 %, and the specific energy consumption only increases from 2.05 kWh/m3 to 2.12 kWh/m3. Therefore, the feed seawater overflush can not only reduce the volume mixing degree of the TC-ERD, but is also a simple and effective means of capacity expansion.